An application programming interface for multiscale shape-material modeling. (November 2021) - Liu, Xingchen; Meneghin, Massimiliano; Shapiro, Vadim
Highlights: Fully extendable API for multiscale structure design and representation. Interoperable shape and material representations through queries. Efficient multiscale point membership query with short-circuit evaluation. Novel multiscale ray-marching algorithm for multiscale structure visualization. Abstract: The application of multiscale structure in mechanical design become increasingly prevalent due to the rapid advancement of modern manufacturing technologies. Over the past few years, a multitude of methods, algorithms, and software have emerged to support the design and representation of such structures. An interoperable solution to connect and compose ad hoc approaches, therefore, could create the network effect to further the advancement of the field. In this paper, we proposed an Application Programming Interface (API) for multiscale structure modeling, which employs a query-based approach to provide interoperability between different shape and material property representations across different scales. The concept of neighborhood is used to link the adjacent scales such that the effective material property of the structure within a neighborhood on the fine-scale equals the material property on the coarse-scale. The use of intrinsic effective material properties enables the interchangeability between different families of fine-scale structures that support a common set of effective properties. The interoperability with downstream applications such as visualization and manufacturing planning is guaranteed through multiscale queries that extend but remains compatible with single scale queries. Such capability is demonstrated through a novel multiscale ray-marching algorithm. We discuss several usage scenarios and provide exemplary implementations of the core interfaces and functionalities of the proposed multiscale API.